Clinical Laboratory Aspect of Carbapenem-Resistant Enterobacteriaceae - Chang-Eun Park (Korean Journal of Clinical Laboratory Science, 2020)
The correct distinction of carbapenem-resistant Enterobacteriaceae (CRE) and ccarbapenemase producing Enterobacteriaceae (CPE) and the rapid detection of CPE are important for instituting the correct treatment and management of clinical infections. Screening protocols are mainly based on cultures of rectal swab specimens on selective media followed by phenotypic tests to confirm a carbapenem-hydrolyzing activity, the rapid carbapenem inactivation method, lateral flow immunoassay, the matrix-assisted laser desorption ionization–time-of-flight test and molecular methods. The CPE is accurate for detection, and is essential for the clinical treatment and prevention of infections. A variety of phenotypic methods and gene-based methods are available for the rapid detection of carbapenemases, and these are expected to be routinely used in clinical microbiology laboratories. Therefore, to control the spread of carbapenemase, many laboratories around the world will need to use reliable, fast, high efficiency, simple and low cost methods. Optimal effects in patient applications would require rapid testing of CRE to provide reproducible support for antimicrobial management interventions or the treatment by various types of clinicians. For the optimal test method, it is necessary to combine complementary test methods to discriminate between various resistant bacterial species and to discover the genetic diversity of various types of carbapenemase for arriving at the best infection control strategy.